2022
DOI: 10.3390/ijms232415892
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies of Salt Tolerance at the Seed Germination Stage and Yield-Related Traits in Brassica napus L.

Abstract: Salt stress severely affects crop growth and development and reduces the yield of Brassica napus. Exploring natural genetic variations for high salt tolerance in B. napus seedlings is an effective approach to improve productivity under salt stress. Using 10,658 high-quality single nucleotide polymorphic (SNP) markers developed by specific-locus amplified fragment sequencing (SLAF-seq) technology, genome-wide association studies (GWAS) were performed to investigate the genetic basis of salt tolerance and yield-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…With the advance of next-generation sequencing (NGS) technology, mega-level SNPs or genetic variations via whole genome resequencing in population could detect more loci for the yield traits in crops (Zhang et al, 2022a). Using 10,658 high-quality SNP markers, a total of 497 SNPs were detected to associate with yieldrelated traits in B. napus (Zhang et al, 2022b). Based on highquality 670,028 SNPs, GWASs were conducted using multi-locus random mixed linear model for 11 important traits in rapeseed (Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of next-generation sequencing (NGS) technology, mega-level SNPs or genetic variations via whole genome resequencing in population could detect more loci for the yield traits in crops (Zhang et al, 2022a). Using 10,658 high-quality SNP markers, a total of 497 SNPs were detected to associate with yieldrelated traits in B. napus (Zhang et al, 2022b). Based on highquality 670,028 SNPs, GWASs were conducted using multi-locus random mixed linear model for 11 important traits in rapeseed (Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Under salt stress, early responsive dehydration 1 ( ERD1 ) has been reported to have upregulation in multiple studies ( Liu et al., 2022 ). Similarly, Open Stomata 2 ( OST2 ) which encodes a plasma membrane H + ATPase is crucial for ion homeostasis during salinity stress ( Zhang et al., 2022 ). Earlier, PgMyb88 was also proposed to have a role under salt stress in pearl millet ( Chanwala et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…To know the genetic basis of salt tolerance in rapeseed a GWAS was conducted on a diverse panel of 146 accessions using 10,658 high quality SNP markers ( Zhang et al., 2022b ). In this study 77 SNPs were identified having significant associations with salt tolerance traits, out of which 36 SNPs were associated with three salt tolerance traits (germination vigor, germination rate, relative salt damage index) and gene ontology annotations revealed 19 candidate genes having putative roles in response to salt stress.…”
Section: Genome-wide Association Mapping Approach For Investigating C...mentioning
confidence: 99%